Social Security in Complex Societies - Lima, Fabio Lucas de Albuquerque (Revista ANPPREV de Seguridade Social, 2025)
Social Security was constitutionally designed to meet the needs of the community in the face of growing social risks (Balera, 2010). Rapid economic development has brought with it an increase in risks (Resende Ruba, 2023). Unemployment, the risk of accidents, incapacity for work, death itself, and old age are factors that are at stake in the social protection guaranteed by public social assistance and social security policies.